2014
DOI: 10.1155/2014/685204
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxylate, a New Marker Metabolite of Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) is characterized by a variety of metabolic impairments that are closely linked to nonenzymatic glycation reactions of proteins and peptides resulting in advanced glycation end-products (AGEs). Reactive aldehydes derived from sugars play an important role in the generation of AGEs. Using metabolite profiling to characterize human plasma from diabetic versus nondiabetic subjects we observed in a recent study that the reactive aldehyde glyoxylate was increased before high levels of plasma gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 61 publications
(56 reference statements)
3
43
0
Order By: Relevance
“…Twenty-four metabolites changed specifically in the plasma of db/db mice (Table 2), of which 12 remained significant after p value adjustment. Besides increases in glucose, elevated levels of glyoxylate were found, which we recently described as a diabetes marker [10]. In addition, corticosterone and 18-hydroxy-11-deoxycorticosterone concentrations were markedly elevated.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Twenty-four metabolites changed specifically in the plasma of db/db mice (Table 2), of which 12 remained significant after p value adjustment. Besides increases in glucose, elevated levels of glyoxylate were found, which we recently described as a diabetes marker [10]. In addition, corticosterone and 18-hydroxy-11-deoxycorticosterone concentrations were markedly elevated.…”
Section: Resultsmentioning
confidence: 78%
“…ESM Table 3 displays the overall significance of the clusters reached for the two knockout models as compared with wild-type mice. Five metabolite clusters displayed high significance for both knockout models (clusters 4,8,10,13,15), consisting of phospholipids, triacylglycerols, AAA and BCAA, as well as glycine, histidine and trans-4-hydroxyproline. Interestingly, four clusters (clusters 1, 5, 9, 11)-mainly consisting of amino acids, hexoses and catabolites-showed overall significant changes only between db/db and C57BLKS/J wild-type mice.…”
Section: Resultsmentioning
confidence: 99%
“…SRC-1), depletion of which can result in increased glucose uptake, enhanced insulin sensitivity, and resistance to age-associated obesity and glucose intolerance (Wang et al, 2012). A literature review revealed additional Steiner nodes with known relevance to disease, including the metabolite glyoxylic acid, which has been characterized as a marker metabolite for type 2 diabetes (Nikiforova et al, 2014). Thus, our model incorporates many predicted nodes with known relevance to these conditions, though many are not well-established actors in these contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have identified glyoxylate as a biomarker for early detection of Type 2 diabetes (Nikiforova et al, 2014). In our study, we measured little variation between glyoxylate levels in the diabetic cornea compared to healthy controls (Figure 3).…”
Section: Resultsmentioning
confidence: 99%